Enhancing English Vocabulary Mastery through the Scramble Model: A Classroom Action Research in Grade V of SD Tri Bakti Medan Marelan - Harry Sambayu; Lisa Fitri Meidipa (Indo Publishing, 2026)
through the implementation of the scramble learning model within a Classroom Action Research (CAR) framework. The research was motivated by students’ difficulties in spelling vocabulary correctly, interpreting word meanings, pronouncing vowels accurately, and constructing grammatically sound sentences. The scramble model was applied over two learning cycles, incorporating group-based word games that required students to rearrange jumbled letters into correct vocabulary and use them in sentence formation. The study involved 25 students, with a minimum mastery criterion of 76 and a classical completeness target of 80%. Results showed a significant improvement: classical completeness increased from 65.66% in cycle I to 87.5% in cycle II, and the average score rose from 76.25 to 86.54. Gains were observed across all vocabulary indicators—form, meaning, pronunciation, and usage. These findings align with previous studies indicating that the scramble model is effective for enhancing vocabulary acquisition in elementary education. Therefore, the scramble model is recommended as an engaging, practical, and contextually relevant strategy for vocabulary instruction in primary schools.